The Effect of Doxycycline Hyclate, Chlorhexidine Gluconate, and Minocycline Hydrochloride on Osteoblastic Proliferation and Differentiation In Vitro - Almazin, Salah M.; Dziak, Rosemary; Andreana, Sebastiano; Ciancio, Sebastian G. (Journal of periodontology (1970), 2009)
Background: The purpose of this study was to determine the effect of the active substance of three types of local delivery systems, doxycycline hyclate 10% (DOXY), chlorhexidine gluconate, 2.5 mg (CHX), and minocycline hydrochloride, 1 mg (MINO), on osteoblastic cell proliferation and differentiation. Methods: There were four groups: control osteoblastic cells (OB) alone, OB + DOXY, OB + CHX, and OB + MINO. Trypan blue and MTT [3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide] assays were used to test osteoblastic cell viability. Cell differentiation was tested by measuring alkaline phosphatase levels. Osteoblast morphology was investigated by light and scanning electron microscopy. Results: At a concentration of 0.5 mg/ml, the Trypan blue test showed that DOXY, MINO, and CHX had significant toxicity effects on osteoblast cells compared to the control group, with a mean cell viability of 84%, 74%, and 51%, respectively (P <0.05). The MTT test showed that the control and DOXY groups were statistically significantly different (P <0.05) compared to CHX and MINO groups. The DOXY group showed a significantly higher alkaline phosphatase activity (∼56%) than the control and MINO groups, and it was nearly 178% higher than the CHX group (P <0.05). The morphology of the osteoblasts seemed to be slightly altered when they were incubated with DOXY; however, with MINO, they appeared rounded with minimal attachment. In the CHX group, the osteoblasts assumed a shape of a very thin filopodia with a volcano‐like nucleus. Conclusions: At a concentration of 0.5 mg/ml, CHX and, to a lesser extent, MINO had a cytotoxic effect on osteoblast proliferation in vitro. However, DOXY seemed to enhance maturation and differentiation rather than proliferation. In addition to DOXY's beneficial effect as an adjunctive therapy to mechanical debridement in the treatment of periodontal disease, it may have an effect on periodontal regeneration.